THE RELATIONSHIP BETWEEN PHONEMES AND MEANING: AN IN-DEPTH ANALYSIS (SCIENCE TIME JOURNAL, 2025)
This article offers a comprehensive synthesis of theoretical, experimental, typological, developmental, and neurocognitive evidence on the complex relationship between phonemes and meaning, arguing that the traditional Saussurean notion of pure arbitrariness must be tempered by systematic tendencies that shape lexical structure and lexical access. The first section revisits foundational theory Saussure’s model of the linguistic sign and Jakobson’s work on phonological function while tracing historical observations of phonesthemes and phonosemantic clusters that suggest sub-lexical patterns can bias semantic interpretation. By integrating classical linguistics with contemporary corpus-driven and experimental approaches, the article frames the debate as one between combinatorial convention and perceptually grounded iconicity rather than as an either/or dichotomy.